The Effects of Occupational Stress on Quality of Life and Associated Factors among Hospital Nurses in Iran - Jafari, Samira; ., Azizollah Batebi; ., Mostafa Hosseini; ., Mitra Ebrahimpoor; ., Fatemeh Shojaei, Maryam Vaezi (Journal of Social and Development Sciences, 2012)
Nurses deal with many crises at work. It is obvious that being exposed to stress for long, results in severe physical and mental complications and affects individual is welfare. This study was aimed at determining the quality of life (QOL) of nurses and whether there is any relation between occupational stress and QOL. This analytical-descriptive cross sectional study was carried out in University hospitals of Zanjan, Iran. 241 nurses were sampled using proportional to size stratified method. The data were collected by means of Iranian version of the Short Form Health Survey (SF-36) and a questionnaire on demographic information and work factors. Occupational stress was measured by Toft Gray and Anderson’s tool. The questionnaires were filled by nurses themselves and the data were analyzed by Spearman’s Correlation test, Kruskal-Wallis and one-way ANOVA and Enter-method Regression with SPSS 16.0 software. The results showed a high level of occupational stress among nurses, which adversely affected their quality of life. According to the results QOL of male and female nurses differ with men having a higher QOL and less occupational stress. 2 work factors, satisfaction and others positive attitude towards nursing, affected all dimensions of QOL and occupational stress. There was no significant correlation between QOL or occupational stress and factors like position, shift, ward, experience, time off, overtime hours, interest in desertion and education. According to harmful effects of occupational stress on nurses, cognitive-behavioral interventions, learning coping strategies are proposed.